2019
DOI: 10.1111/1742-6723.13414
|View full text |Cite
|
Sign up to set email alerts
|

Review article: End‐of‐life care for older people in the emergency department: A scoping review

Abstract: Older people are increasingly utilising emergency services, often at the end of their life. This scoping review aimed to provide a comprehensive understanding of available research regarding end-of-life (EOL) care for older people in the ED. The Joanna Briggs Institute scoping review methodology guided this review. Databases of CINAHL, Ovid MEDLINE, Embase, SocINDEX and Google Scholar were searched using a combination of terms, including older/aged/geriatrics/elderly, palliative/terminal/end-of-life and emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…The Acute Frailty network in the UK is an example of a whole systems approach for older people admitted to hospital and has shown improvement in patient outcomes [ 98 ]. A research priority identified by the European Society for Emergency Medicine Geriatric Emergency Medicine [ 4 ] section and the European Geriatric Medicine Society GEM Special Interest Group is to identify if elements of CGA are effective in improving outcomes for older patients [ 83 ]. Other key research questions included what community interventions are safe and effective to prevent adverse outcomes for older adults following discharge from the ED.…”
Section: Discussionmentioning
confidence: 99%
“…The Acute Frailty network in the UK is an example of a whole systems approach for older people admitted to hospital and has shown improvement in patient outcomes [ 98 ]. A research priority identified by the European Society for Emergency Medicine Geriatric Emergency Medicine [ 4 ] section and the European Geriatric Medicine Society GEM Special Interest Group is to identify if elements of CGA are effective in improving outcomes for older patients [ 83 ]. Other key research questions included what community interventions are safe and effective to prevent adverse outcomes for older adults following discharge from the ED.…”
Section: Discussionmentioning
confidence: 99%
“…There is general consensus that delivering high-quality end-of-life care in the ED is an unmet need. 14 Compared with dying at home or in a hospice facility, quality of dying in the hospital is worse and may lead to protracted grief and psychological distress for families. 4 Time constraints, patient volume, and environmental factors may contribute to suboptimal patient care and family experience.…”
Section: Discussionmentioning
confidence: 99%
“…Esse dado pode ser útil para informar o planejamento de políticas de saúde e estratégias comunitárias que podem garantir que o atendimento mais adequado seja prestado no local mais apropriado para idosos em fim de vida. Um exemplo seria defender a inscrição precoce em cuidados paliativos (HUANG YL. et.…”
Section: Resultsunclassified